HUBUNGAN MOTIVASI DAN FLEKSIBILITAS TERHADAP HASIL BELAJAR SENAM LANTAI GULING DEPAN - Prakoso, Satrio Agung; Simanjuntak, Victor; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this study is, does motivation and flexibility have a significant relationship to the learning outcomes of front roll floor gymnastics in class X SMA Negeri 4 Pontianak. The method in this study is the descriptive correlational method by connecting the variables used in this study. The population in this study was class X students of SMA Negeri 4 Pontianak with a total sample of 3 class X namely X MIPA3, X MIPA4 and X MIPA5. Data analysis uses correlation coefficient analysis. Based on the data processing done, it was found that motivation and correlation to XMIPA 3 learning outcomes, whereas in class X MIPA4 and X MIPA5 only motivation correlated with learning outcomes of front roll floor gymnastics, while flexibility did not have a correlation to learning outcomes.Â Keywords: Fleksibility, Front Bolster Gymnastics, MotivationÂ